Analisis Cerita Rakyat Mandailing “Sampuraga”: Suatu Kajian Pendekatan Objektif dan Nilai Pendidikan Karakter - Nikmah Sari Hasibuan; Irman Puansyah; Ahmad Yamin Hasibuan (Universitas Negeri Medan, 2020)
His study aims to analyze the values of character education in the folklore of Sampuraga that developed in the Mandailng Natal community. This research uses descriptive analytical method, which is a method that is as clear as possible about the object under study, as well as describing the data as a whole, systematically, and accurately. The analysis is carried out using the theoretical basis used, then analyzed and interpreted in accordance with the study of theory so that the results of the research will be able to describe the problems studied objectively, systematically based on the theories the authors use. Based on the results of this study it can be concluded that first, the principle of an objective approach in the process of applying the elements that make up the literary work itself, such as plot, setting, characterization, language style, and perspective. An objective approach to Sampuraga Folklore. Second, there are four values of character education in the folklore of Sampuraga and Nasondang Ngilong-Ilong, namely the value of religious character education, compassion, hard work, and honesty.